2019
DOI: 10.1021/acsanm.9b00215
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of Three-Dimensionally Ordered Porous TiO2 Decorated with Pt and Reduced Graphene Oxide for the Visible-Light Photocatalytic Degradation of Waterborne Pollutants

Abstract: A new photocatalyst was developed by coupling threedimensionally ordered macroporous (3DOM) TiO 2 with platinum (Pt) and reduced graphene oxide (rGO) for water purification applications under visible light. The rGO/Pt/3DOM TiO 2 ternary photocatalyst was synthesized by codecoration of 3DOM TiO 2 prepared by the colloidal crystal templating approach with Pt nanoparticles and rGO nanosheets via impregnation and in situ reduction methods. Modification with Pt and rGO reduced the band energy and significantly impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 69 publications
0
33
0
Order By: Relevance
“…The fabrications of graphene-based PCs, where graphene-like materials (GO/rGO) act as co-catalysts, has been mostly carried out by immersing/dipping the IO PC into GO colloidal suspension with subsequent post-thermal treatment (calcination) [55,68,69,71]. On the other hand, the formation of graphene-like materials as the backbone material of IO PC requires at least three-step procedure i.e., (i) preparation of template (opal), (ii) infiltration of opal with targeted material, and (iii) the removal of sacrificial template.…”
Section: Graphene-based Photonic Crystalsmentioning
confidence: 99%
“…The fabrications of graphene-based PCs, where graphene-like materials (GO/rGO) act as co-catalysts, has been mostly carried out by immersing/dipping the IO PC into GO colloidal suspension with subsequent post-thermal treatment (calcination) [55,68,69,71]. On the other hand, the formation of graphene-like materials as the backbone material of IO PC requires at least three-step procedure i.e., (i) preparation of template (opal), (ii) infiltration of opal with targeted material, and (iii) the removal of sacrificial template.…”
Section: Graphene-based Photonic Crystalsmentioning
confidence: 99%
“…An important aspect that should be considered for 3D powdered PC-based plasmonic photocatalysts is the periodical/structural integrity as disordered structure could affect the enhancement of the visible-light harvesting, thus reducing the photocatalytic performance. Indeed, the crushed Au/TiO 2 biomorphic (BM)PCs have exhibited lower photodegradation efficiency ( Figure 6) as compared with uncrushed ones [120]. Similarly, C. Dinh et al have shown that the crushed Au/TiO 2 -3D hollow nanospheres (HNSs) show about 4.3-fold lower efficiency of CO 2 generation from photodecomposition of isopropanol as compared with an original Au/TiO 2 -3DHNS, indicating the probability of a decrease in photoabsorption ability by Au, due to the structure disruption [124].…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
“…The time course of the photocatalytic degradation of MO under visible-light irradiation (λ > 420 nm) using bare PCs (TiO 2 -BMPC), Au-modified PCs (Au/TiO 2 -BMPC), crushed Au-modified PCs (Au/TiO 2 -BMPC) and commercial titania modified with Au NPs (Au/TiO 2 -P25): (a) a decrease in the concentration of dye during degradation (C/C 0 ), and (b) the respective logarithm plots; Reprinted with permission (after formatting) from[120]. Copyright (2016) Elsevier.…”
mentioning
confidence: 99%
“…Generally, numerous studies have been demonstrated that the photocatalytic activity of bare anatase and rutile TiO2, is lower than that observed for their anatase/rutile composites [33][34][35][36][37][38][39]. One of the best examples is the P25 commercial material, containing 70-80% of anatase and 30-20% of rutile that produced by Evonik.…”
Section: Introductionmentioning
confidence: 99%